18F-AlF-NOTA-octreotide PET/CT and 3D printing technology for precision diagnosis and treatment of phosphaturic mesenchymal tumors in patients with tumor-induced osteomalacia: two case reports - Zhao, Gang; Guan, Lijuan; Zhang, Yongqiang; Shi, Xingzhen; Luo, Wenming; Yang, Maiqing; Wang, Qi; Liu, Zhen; Liu, Yongqiang; Ding, Xiaolei; Zhao, Jie (Frontiers in Endocrinology, 2024)
Objective: This study aims to report the application of 18F-AlF-NOTA-Octreotide PET/CT and 3D printing technology in the diagnosis and treatment of phosphaturic mesenchymal tumors (PMT) in patients with tumor-induced osteomalacia (TIO). Case presentation: A 68-year-old male patient (Case 1) was admitted to the Weifang People’s Hospital in August 2022 with complaints of “persistent pain in the bilateral flank and lumbosacral region”. 18F-AlF-NOTA-Octreotide PET/CT showed high octreotide expression in the left femoral region. A 48-year-old male patient (Case 2) was admitted to the Weifang People’s Hospital in November 2022, complaining of “pain in the lumbar region and ribs”. 18F-AlF-NOTA-Octreotide PET/CT showed high octreotide expression in the pancreatic uncinate process and the left acetabulum. They were diagnosed with hypophosphatemic osteomalacia, with a strong consideration of an underlying neuroendocrine tumor. Preoperative design of 3D virtual surgery, CAD/CAM, and 3D printing technology were used to customize the digital surgical guide plates, and the surgery was carried out. They were both finally confirmed as phosphateuric mesenchymal tumors (PMT) based on postoperative pathology and immunohistochemistry results. Both patients experienced substantial relief from their clinical manifestations after surgery. Conclusion: 18F-AlF-NOTA-Octreotide PET/CT may be a precise diagnostic method for TIO, while 3D printing technology may serve as an effective and dependable adjunct for the treatment of PMT in patients with TIO.